1986
DOI: 10.1002/ijc.2910380215
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell polyamine levels and host toxicity during continuous alpha‐difluoromethylornithine infusion

Abstract: The dose effects of continuous alpha-difluoromethylornithine (DFMO) infusion on red blood cell (RBC) polyamine levels, host toxicity and tumor growth were determined. Male rats with and without a transplantable methylcholanthrene-induced sarcoma received intravenously either 0.45% NaCl or DFMO at 500 mg, 1,000 mg, or 2,000 mg/kg body wt/day for 6 or 12 days. Dose-related inhibition of tumor growth was noted after the 12-day treatment. There were no changes in host carcass weight, food intake, plasma albumin, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…All rats were anesthesized (Ketamine | 50 mg/kg, i.m.) 4 We have previously demonstrated that this ratio protected the rat from DFMO-induced throm-bocytopenia but did not affect the antitumor activity. When the tumor width was 1.0 cm, two dimensional measurements (cm) were taken every other day and the weight (g) calculated using the formula-length X width 2 x IA [3].…”
Section: Methods and Proceduresmentioning
confidence: 90%
See 2 more Smart Citations
“…All rats were anesthesized (Ketamine | 50 mg/kg, i.m.) 4 We have previously demonstrated that this ratio protected the rat from DFMO-induced throm-bocytopenia but did not affect the antitumor activity. When the tumor width was 1.0 cm, two dimensional measurements (cm) were taken every other day and the weight (g) calculated using the formula-length X width 2 x IA [3].…”
Section: Methods and Proceduresmentioning
confidence: 90%
“…DFMO in a rat-model and in man is thrombocytopenia [4,5]. DFMO in a rat-model and in man is thrombocytopenia [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation